Complementary primary mental health programs for young people in Australia: Access to Allied Psychological Services (ATAPS) and headspace. Issue 1 (December 2017) - Bassilios, Bridget; Telford, Nicolas; Rickwood, Debra; Spittal, Matthew; Pirkis, Jane
Abstract Objective Access to Allied Psychological Services (ATAPS) was introduced in 2001 by the Australian Government to provide evidence-based psychological interventions for people with high prevalence disorders.headspace, Australia's National Youth Mental Health Foundation, was established in 2006 to promote and facilitate improvements in the mental health, social wellbeing and economic participation of young people aged 12–25 years. Both programs provided free or low cost psychological services. This paper aims to describe the uptake of psychological services by people aged 12–25 years via ATAPS andheadspace, the characteristics of these clients, the types of services received and preliminary client outcomes achieved. Methods Data from 1 July 2009 to 30 June 2012 were sourced from the respective national web-based minimum datasets used for routine data collection in ATAPS andheadspace . Results In total, 20, 156 and 17, 337 young people accessed two or more psychological services via ATAPS andheadspace, respectively, in the 3-year analysis period. There were notable differences between the clients of, and the services delivered by, the programs. ATAPS clients were less likely to be male (31 vs 39%) and to reside in major cities (51 vs 62%) thanheadspace clients; ATAPS clients were also older (18–21 vs 15–17 years modal age group). There was some variation in the number and types of psychological sessions that young people received via the programs but the majority received at least one session of cognitive behavioural therapy. Based on limited available outcome data, both programs appear to have produced improvements in clients' mental health; specifically, psychological distress as assessed by the Kessler-10 (K-10) was reduced. Conclusions ATAPS andheadspace have delivered free or low-cost psychological services to 12–25 year olds with somewhat different characteristics. Both programs have had promising effects on mental health. ATAPS andheadspace have operated in a complementary fashion to fill a service gap for young people.